2010
DOI: 10.1021/es103075p
|View full text |Cite
|
Sign up to set email alerts
|

DRIFTS Study of Ammonia Activation over CaO and Sulfated CaO for NO Reduction by NH3

Abstract: CaO catalyzes NH(3) oxidation, while sulfated CaO catalyzes NO reduction by NH(3) in the presence of O(2), and the adsorption and transformation of ammonia over CaO and sulfated CaO has been investigated by in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) to understand their catalytic mechanism. It has been found that ammonia is first adsorbed over Lewis or Brönsted acid sites, and later undergoes hydrogen abstraction giving rise to either NH(2) amide or NH imide intermediates. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…Additionlly, the bands at 1259 and 1150 cm −1 represent the adsorbed NH 3 over Lewis acid sites [37,43,50]. After the sample was purged by Ar for 30 min, the intensity of the bands was unchanged, indicating that the adsorbed NH 3 was relatively stable.…”
Section: Ammonia Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionlly, the bands at 1259 and 1150 cm −1 represent the adsorbed NH 3 over Lewis acid sites [37,43,50]. After the sample was purged by Ar for 30 min, the intensity of the bands was unchanged, indicating that the adsorbed NH 3 was relatively stable.…”
Section: Ammonia Adsorptionmentioning
confidence: 99%
“…It is worth mentioning that the intensity of band at 1540 cm −1 ascribed to the amide species (-NH 2 ) weakened significantly, and the intensity of the bands at 1468 and 1405 cm −1 due to NH 4 + on Brønsted acid sites [43,45] decreased relatively slightly. During this process, the intensity of the bands at 1259 and 1150 cm −1 due to coordinate ammonia species on Lewis acid sites [37,43,50] and the intensity of bands at 3338 and 3228 cm −1 in the N H stretching region varied slightly, due to the compensation from the gaseous or weakly adsorbed NH 3 (964 cm −1 ). After the catalyst was purged with NO + O 2 for 10 min, the bands at 1060 cm −1 (linear nitrite) and 1610 cm −1 (v(ONO), bridged nitrate) could be observed and the intensity of the bands increased with time.…”
Section: The Reaction Between Nh 3 Ad-species and No + O 2 On Mno X /mentioning
confidence: 99%
“…Mn/bauxite shows two bands at 1236 and 1329 cm −1 owing to the coordination of NH 3 on Lewis acid sites. Other two bands at 1489 and 1438 cm −1 in bauxite may be assigned to -NH 2 vibration and anti-symmetric bending vibration of NH 4 + ions on Brønsted acid sites, respectively 3334. In Mn/bauxite, the band at 1387 and 1498 cm −1 represent −NH 2 vibration on Brønsted acid sites.…”
Section: Resultsmentioning
confidence: 99%
“…The in situ DRIFTS experiments of NH 3 adsorption over sulfated CaO in our previous study indicated that NH 3 adsorbed over both Lewis acid sites and Brønsted acid sites[30]. CO 2 and SO 2 , as the acidic gas may influence the NH 3 molecule adsorbed over Lewis acid sites, and thus influence the SCR reaction.…”
mentioning
confidence: 93%